Menelusuri Jalan Raya Pos Deandels Jakarta-Bogor Abad ke 19 - Muhammad Zaqi al zamani (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
This article is entitled “Traveling the 19th Century Daendels BataviaBuitenzorg Post Road”. The Daendels highway itself is a postal road with a length of 1,000 kilometers in Java that stretches from Anyer to Panarukan. Seeing this aspect, the researcher is interested in studying this problem in depth, so the purpose of this research is to understand the background of the construction of the postal highway, as well as the impact of the postal highway construction. Then to obtain credible results, the research method used is the historical method with steps in the form of: heuristics, verification, interpretation and historiography. From this research it was found that the postal highway (De Grote Postweg), was built in 1808-1811 by order of the Governor General of the Dutch East Indies, namely Herman Willem Daendels. The creation of smooth communication between regions along the island of Java which at that time was controlled by Daendels was the goal of the construction of the postal highway itself, besides that the construction of the postal highway served as a defense against British attacks on the North Coastof Java.